Aquatic live animal radiotracing studies for ecotoxicological applications: Addressing fundamental methodological deficiencies. (November 2017) - Cresswell, Tom; Metian, Marc; Golding, Lisa A.; Wood, Mike D.
Abstract: The use of live animal gamma radioisotope tracer techniques in the field of ecotoxicology allows laboratory studies to accurately monitor contaminant biokinetics in real time for an individual organism. However, methods used in published studies for aquatic organisms are rarely described in sufficient detail to allow for study replication or an assessment of the errors associated with live animal radioanalysis to be identified. We evaluate the influence of some important methodological deficiencies through an overview of the literature on live aquatic animal radiotracer techniques and through the results obtained from our radiotracer studies on four aquatic invertebrate species. The main factors discussed are animal rinsing, radioanalysis and geometry corrections. We provide examples of three main techniques in live aquatic animal radiotracer studies to improve data quality control and demonstrate why each technique is crucial in interpreting the data from such studies. The animal rinsing technique is also relevant to non-radioisotope tracer studies, especially those involving nanoparticles. We present clear guidance on how to perform each technique and explain the importance of proper reporting of the validation of each technique for individual studies. In this paper we describe methods that are often used in lab-based radioecology studies but are rarely described in great detail. We hope that this paper will act as the basis for standard operating procedures for future radioecology studies to improve study replication and data quality control. Graphical abstract: Highlights: Live radiotracer techniques provide real-time analysis of contaminant accumulation. Technique allows for greater data generation from fewer animals. Methods described in literature are often not detailed enough for study validation. Procedures for animal rinsing, live radioanalysis and geometry correction described.